A Pedagogical look of value added as an indicator of university social relevance (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2017)
The use of systems that allow the measurement of processes within educational systems has been generalized in almost all countries of the world. The measurement allows determining in the first instance the performance conditions of the students and the administrative and related processes that are developed in it, in this sense the state education policies worldwide have generated a special interest in value-added models, This is why this article seeks to give a pedagogical look to this concept in higher education institutions, as an indicator of university social relevance. The main purpose is to find determining elements of a model that allows to integrate the learning strategies defined by the philosophical current of each institution to the results of the measurements of the added value. Within the results found through text mining, it was found that the concept of added value is associated with terms such as: high achievements, punctuation, models, measurements, contribution, difference. In addition, it is related to factors such as: education. Students, school and production. These factors constitute the fundamental elements for the definition of a value-added monitoring model in higher education institutions
Keywords: added value; relevance; higher education; pedagogy